Barriers and practices in pain management for intubated patients: A study of critical care nurses in Southern West Bank hospitals - Ibrahim Salim; Moath Abu Ejheisheh; Ahmad Ayed; Ibrahim Aqtam; Ahmad Batran (PLoS ONE, 2025)
Introduction Effective pain management is vital for intubated patients in intensive care units, as these individuals cannot verbally communicate their discomfort. The knowledge, attitudes, practices, and perceived obstacles of nurses are critical factors that influence successful pain management. Objective This study aimed to evaluate the knowledge, attitudes, practices, and perceived obstacles faced by critical care nurses regarding pain management in intubated patients within hospitals located in Southern West Bank. Methods A cross-sectional survey was carried out with 199 critical care nurses utilizing the Nurses’ Knowledge and Attitudes Survey Regarding Pain, alongside a modified tool for assessing perceived barriers to pain management. The data collected were analyzed to pinpoint deficiencies in knowledge and barriers impacting effective pain management strategies. Results The analysis showed that 192 out of 199 nurses (96.5%) lacked sufficient knowledge regarding pain management. System-related barriers, including the lack of standardized protocols and ineffective communication with physicians, were frequently identified as obstacles, averaging a score of 2.41 out of 3. Additionally, nurse-related barriers comprised insufficient time for providing non-pharmacological interventions (73.9%) and a lack of confidence in utilizing assessment tools (43.7%). Patient-related issues, such as difficulties in communication (72.4%) and hesitancy to report pain (58.8%), were also noted. A notable difference in knowledge scores was observed based on prior education in pain management, with those having received training (41.7%) performing better. Conclusion The findings underscore the need for focused educational initiatives, the establishment of standardized protocols for pain management, and enhanced interdisciplinary communication. These improvements are essential for optimizing pain management practices and ensuring better patient outcomes. The results suggest that addressing knowledge gaps and systemic barriers could lead to significant enhancements in patient care and health policies.